The Humoral Cosmos: Astrological Medicine and the Birth of Evidence-Based Timing in Pre-Modern Clinical Practice - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2026)
Astrological medicine (iatromathematics) dominated pre‑modern clinical practice from the 11th to 17th centuries, yet it is routinely dismissed as superstitious pseudoscience. This verdict obscures its methodological contribution to clinical reasoning. This article reevaluates astrological medicine as a proto‑evidence‑based system, arguing that it created the first systematic practice of using temporally indexed observational data to guide clinical decisions concept we term “evidence‑based timing.” Methods: A historical analysis of primary sources (Galen’s De diebus decretoriis, Avicenna’s Canon, Bernardo de Gordon’s Lilium medicinae), material instruments (ephemerides, astrolabes, Zij tables, Zodiac Man diagrams), and case records (Simon Forman, Richard Napier, Girolamo Fracastoro) was conducted, tracing the logic of astrological prognosis and its secularization through Sanctorius and Sydenham. Astrological medicine forced practitioners to record celestial configurations, predict critical days, and verify outcomes, producing longitudinal, and time‑stamped clinical data. While lacking randomization, blinding, and statistical inference, it institutionalized the habit of temporal optimization. The doctrine of decumbiture charts and lunar‑phase bloodletting schedules represented the first standardized risk‑assessment tools. By the 17th century, iatromathematicians stripped away planetary causation but preserved the chronometric framework, leading directly to quantitative physiology and secular crisis‑day prognosis. Pre‑modern physicians were rational empiricists who asked the right question—“When?” even with the wrong causal model. Astrological medicine was not evidence‑based by RCT standards but was authentically evidence‑based timing. Historians should replace dismissive labels of “superstition” with contextual analyses that recognise the empirical discipline of astrological clinical practice, while modern chronobiologists should acknowledge this lineage.